PERAN ORANG TUA TERHADAP PERTUMBUHAN IMAN ANAK DI GEREJA KELUARGA TABGHA ALMA JAYA MALAYSIA - Djaafar, Andre; Setiawan, Eko Agus; Siringoringo, Marito; Purba, Gomgom (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
Parents are men and women who are bound by marriage and are ready to assume responsibility as the father and mother of the children they give birth to. Parents are two different individuals entering life together by bringing views, daily habits. The writer of Proverbs also emphasized to parents to use the